1986
DOI: 10.2307/2408603
|View full text |Cite
|
Sign up to set email alerts
|

The Biogeographic Evidence Supporting the Pleistocene Forest Refuge Hypothesis

Abstract: The prevailing explanation for the observed distributional patterns and areas of endemism of tropical forest organisms is the Pleistocene refuge hypothesis, which proposes that wide-ranging ancestral taxa were isolated into forest refuges during certain glacial periods, and that this isolation provided them with the opportunity to speciate. John Endler has recently argued that two predictions of the refuge hypothesis-that contact zones between vicars should be between refuges and that contact zones of rapidly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
160
1
10

Year Published

1999
1999
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(178 citation statements)
references
References 17 publications
(6 reference statements)
7
160
1
10
Order By: Relevance
“…Centers of diversity correspond with zones of relative environmental uniformity, and zones of biotic change correspond with zones of environmental change. Mayr and O'Hara (1986) refuted this hypothesis with respect to the fauna of tropical Africa. Similarly, biogeographical data sets from South America do not support the Gradient hypothesis (Prum, 1988;Patton et al, 1992), whereas Mallet (1993) found "it is not easy to exclude parapatric differentiation" as a mode of speciation in Amazonian Heliconius butterflies (see, however, Futuyama and Shapiro 1995).…”
Section: Gradient Hypothesismentioning
confidence: 94%
“…Centers of diversity correspond with zones of relative environmental uniformity, and zones of biotic change correspond with zones of environmental change. Mayr and O'Hara (1986) refuted this hypothesis with respect to the fauna of tropical Africa. Similarly, biogeographical data sets from South America do not support the Gradient hypothesis (Prum, 1988;Patton et al, 1992), whereas Mallet (1993) found "it is not easy to exclude parapatric differentiation" as a mode of speciation in Amazonian Heliconius butterflies (see, however, Futuyama and Shapiro 1995).…”
Section: Gradient Hypothesismentioning
confidence: 94%
“…Both cooling and precipitation changes (often drying) and low CO 2 levels associated with glacial periods have been important, causing contractions of wet lowland forest [16], the extent of which remain the subject of ongoing debate [17,18]. Remnant rainforest areas have been hypothesized as glacial refugia for many organisms, for example, in Africa [19][20][21] and the New World [22]. Empirical studies have provided indirect or less commonly direct evidence that species distributions and endemism patterns can indeed be associated with Quaternary-scale habitat stability in tropical areas [7,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…The spatial extent of the gap has varied in response to glaciation with Africa becoming more arid and the Dahomey Gap wider during glacial periods at higher latitudes. This dynamic process has led several authors to suggest that the high species diversity across the Guineo-Congolian rainforest might have arisen as a consequence of the formation of two primary refugia located in the Upper and Lower Guinea forest blocks, enabling population differentiation in allopatry, followed by putative secondary contact as forests expanded during interglacial periods (Mayr and O'Hara 1986). This basic premise has been expanded upon by other authors, leading to a more nuanced view of the number of refugia distributed across the Guineo-Congolian rainforest.…”
mentioning
confidence: 99%